2013
DOI: 10.1016/j.jvs.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of covered stents versus bare metal stents for treatment of chronic atherosclerotic mesenteric arterial disease

Abstract: In this nonrandomized study, CS were associated with less restenosis, recurrences, and reinterventions than BMS in patients undergoing primary interventions or reinterventions for CMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 29 publications
1
71
0
4
Order By: Relevance
“…4). In order to avoid the consequences of a potential vessel perforation as well as to reduce the rate of late restenosis, stent grafts can be deployed as well [21]. …”
Section: Are Endovascular Techniques a Reasonable Treatment Option?mentioning
confidence: 99%
“…4). In order to avoid the consequences of a potential vessel perforation as well as to reduce the rate of late restenosis, stent grafts can be deployed as well [21]. …”
Section: Are Endovascular Techniques a Reasonable Treatment Option?mentioning
confidence: 99%
“…In general, while the reintervention rate appears higher for ET, the method has been considered cost-effective and provides an improvement in quality-adjusted life years [27] . Some authors have suggested ET as first-line treatment, with the caveat that angioplasty should be combined with stenting using covered stents rather than bare-metal stents (based on limited retrospective data), as this approach seems to deliver better freedom from restenosis and symptom recurrence [18,28] . The results of our study are similar to those previously reported in the literature, finding that OT delivers better midand long-term patency rates.…”
Section: Resultsmentioning
confidence: 99%
“…Options include the iCast covered stent (Atrium, Hudson, NH). Additionally, in a recent comparison of CS versus BS, CS were associated with improved freedom from restenosis (92% vs 53%), symptom recurrence (92% vs 50%), primary patency at 3 years (92% vs 52%) (12). Further, improved rates of restenosis, symptom recurrence, and patency were also seen in patients undergoing reintervention for chronic mesenteric ischemia.…”
Section: Procedural Stepsmentioning
confidence: 93%